O mito da literatura de autoajuda: uma análise crítica da linguagem e da tipologia dos heróis presentes em na margem do rio Piedra eu sentei e chorei e homens são de Marte, mulheres são de Vênus - Oliveira, Nilsamira da Silva (2007)
The self-help literary genre is a mass editorial phenomenon — a product of the cultural industry - absorbed by thousands and thousands of readers around the world. Such genre is made up of manuals, essays, narratives, individual statements, etc. by means of which the editorial market - that controls this sort of textual production - trades formulas, techiques, advice, in order to solve the problems that afflict individuals in modern times. The linguistic procedures that dominate self-help text structures are designed starting from appellative premises aiming at making it easier the circulation and reception of the text referred to, among the reading public who consumes messianic-like advice. And facilitation occurs through approaches based on stereotypes, clichés, conventions and sociocultural concepts that maintain the social prevailing order. Brazilian market of self-help books has grown over 700%, from 1994 to 2002, whereas the editorial market as a whole, has grown only 35%. In this paper, we focus on investigations about the amazing success of the textual genre studied, through literary criticism procedures about the self-help books: On the Piedra's River Bank I sat and cried, whose author is the Brazilian writer Paulo Coelho, as well as Man come from Mars and Women come from Venus, by the North-American John Gray.